An Investigation of the Effective Concrete Slab Width for Composite Construction - Hagood, Thomas A.; Guthrie, Lucian; Hoadley, Peter G. (Engineering Journal, 1968)
This paper describes an experimental investigation for determining the effective width of a concrete slab acting compositely with a series of three rolled steel beams. The program was conducted by the Department of Civil Engineering at Vanderbilt University under the sponsorship of the American Iron and Steel Institute. The object of the program was to determine actual effective slab widths and compare them with allowable values as specified by the 1963 edition of the AISC Specification for the Design, Fabrication and Erection of Steel for Buildings. One can conclude from this study, at least within the range of parameters tested by both the authors and by Mackey and Wong, present effective slab width requirements for composite construction are conservative for interior beams. On the other hand, the results indicate that present specification requirements are reasonable for exterior beams.